Implikasi Perkembangan Teknologi Terhadap Relasi Warga Negara Di Era Kontemporer - Razwa Naiakarya Adila Permana; Rizki Fadillah (JURNAL ILMIAH NUSANTARA, 2026)
The development of digital technology in Indonesia has brought about major changes in the way people interact, participate in the political process, and relate to government institutions. This study seeks to examine the influence of communication technology, social media, and the digitization of public services on the dynamics of citizenship today. This study was conducted through an analysis of various scientific sources, relevant regulations, and empirical findings on technological transformation and the implementation of e-government. The findings show that technology makes it easier for people to obtain information, opens up broader opportunities for participation, and shapes more responsive and two-way communication patterns. However, various obstacles still arise, such as unequal access to technology, uneven levels of digital literacy, the threat of misinformation, and the inconsistent implementation of digital government services across regions. This study concludes that technological developments have the potential to strengthen the relationship between citizens and the state if supported by inclusive policies, increased digital capabilities of the community, and more equitable access to technology. Without these efforts, technological developments could actually widen social inequality and reduce the quality of the relationship between citizens and the government.